PENGARUH MODEL PROJECT BASED LEARNING BERMEDIAKAN COUPLE CARD TERHADAP HASIL BELAJAR IPA SISWA KELAS III - Luh Putri Bhawanayani; Ni Wayan Rati; Luh Putu Putrini Mahadewi (Jurnal Pendidikan dan Pembelajaran IPA Indonesia, 2018)
AbstrakPenelitian ini dilakukan berdasarkan pada permasalahan berikut. 1) Kurangnya penggunaan model pembelajaran. 2) Kurangnya pemanfaatan media pembelajaran. 3) Rendahnya hasil belajar IPA siswa. Penelitian bertujuan untuk mengetahui perbedaan yang signifikan hasil belajar IPA antara kelompok siswa yang dibelajarkan melalui model project based learning bermediakan couple card dan kelompok siswa yang tidak dibelajarkan melalui model project based learning bermediakan couple card pada kelas III SD di Gugus I Kecamatan Seririt Kabupaten Buleleng Tahun Pelajaran 2017/2018. Jenis penelitian adalah penelitian eksperimen semu dengan rancangan post-test-only control group design. Populasi adalah kelas III di Gugus I Kecamatan Seririt sebanyak 6 kelas dan sampel penelitian pada kelas ekperimen SDN 1 Kalianget berjumlah 15 orang dan SDN 2 Kalianget berjumlah 12 orang, ditentukan dengan teknik random sampling. Pengumpulan data menggunakan metode tes yang mengukur hasil belajar IPA. Data dianalisis menggunakan statistik deskriptif dan statistik inferensial (uji-t). Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan hasil belajar IPA antara kelompok siswa yang dibelajarkan melalui model project based learning bermediakan couple card dan kelompok siswa yang tidak dibelajarkan melalui model project based learning bermediakan couple card. Besarnya thitung adalah 4,13, sedangkan ttabel pada taraf signifikan 5 % dan dk = 25 adalah 2,06. Hal ini berarti, thitung > ttabel. Di samping itu, rata-rata skor hasil belajar IPA siswa kelas eksperimen (22,90) lebih tinggi dari pada siswa kelas kontrol (15,17). Maka, model project based learning bermediakan couple card berpengaruh terhadap hasil belajar IPA pada siswa kelas III Sekolah Dasar Gugus I Kecamatan Seririt, Kabupaten Buleleng Tahun Pelajaran 2017/2018. Kata Kunci: Couple Card, IPA, PjBL AbstractThis research was done based on four problems, namely 1) lack of the use of learning model, 2) the usage of learning media, and 3) the decrease of science achievement. The research aims at knowing the significant difference of the science subject’s result between students’ group who were taught through project based learning model mediated by couple card and students group who were not taught through project based learning model mediated by couple card in third grade students of SD in Gugus I Seririt district Buleleng regency in Academic Year 2017/2018. The research was designed as quasi experiment with Post-test-Only Control Group Design. The population of the research were third grade students in Gugus I Seririt district with six classes and the sample of this research in experimental class that was SDN 1 Kalianget were 15 students and SDN 2 Kalianget were 12 students, which was determined by random sampling technique. The data was collected by test method through measure the students’ result of science subject learning. The data was analyzed by using descriptive statistics and inferential statistics (t-test). The result of the research showed that there was a significant difference of the result of the science subject between students’ group who were taught through project based learning model mediated by couple card and students’ group who were not taught through project based learning model mediated by couple card. The result of analysis was tcount = 4,13, while the ttable towards the significant was 5% and dk = 25 was 2,06. It means that tcountis higher than ttable (tcount>ttable). Besides that, the average score of the result of science subject learning of the students’ who were taught through project based learning model mediated by couple card (22,90) is higher than and students’ group who were not taught through project based learning model mediated by couple card(15,17). Therefore, Project based learning model mediated by couple card has an effect towards the science result of third grade students of SD Gugus I Seririt district, Buleleng regency in Academic Year 2017/2018. Keywords: Couple Card, science, PjBL